Determination of dissolved reactive phosphorus (DRP) and dissolved organic phosphorus (DOP) in natural waters by the use of rapid sequenced reagent injection flow analysis - Tue-Ngeun O. (2014)
A FI system for rapid sequential determination of dissolved reactive and organic phosphate is described. It utilizes on-line UV photo-oxidation for digestion of dissolved organic phosphate (DOP) with detection of the phosphate produced as phosphomolybdenum blue at 690 nm after reduction of phosphomolybdate with tin(II) chloride. Two injections are performed in the analysis of each sample: the first of sample solution alone enables DRP determination, while the second is of sample plus alkaline peroxydisulfate solutions, which under the photo-oxidation conditions used converts DOP to DRP. The DOP content is evaluated from the difference of the two injections. The digestion efficiency for DOP, evaluated using a range of model organic P compounds of varying stability was greater than 97%. Calibrations were linear over the range of 0.01-6.00 mg P l-1 for both DRP and DRP + DOP graphs, with a detection limit (3 s) of 0.01 mg P l-1 for both species. Relative standard deviations were 0.3% (n = 11, 0.50 mg P l -1) for the DRP determination and 1.0% (n = 11, 0.50 mg P l -1) for the DRP + DOP determination. Injection throughput of 22 h-1 was achieved. The proposed system was validated by analysis of the certified reference materials and comparison with the previous flow injection system. Additional advantage of this system is that it requires the use of only small amounts of the oxidant, with the result that nuisance gas bubble formation is correspondingly minimized. © 2004 Elsevier B.V. All rights reserved.